Sistem Pendukung Keputusan Untuk Menentukan Mutasi Karyawan dengan Menggunakan Metode Oreste (Studi Kasus: PDAM Tirta Deli Kab. Deli Serdang) - Ayu Octavia (JURIKOM (Jurnal Riset Komputer), 2019)
Movements include attitudes, commitment, achievement, age based on the highest level of achievement. From experience and not wrong in making these decisions and the absence of feeling bored or bored in job placement due to the quality of workers who do not match the existing standards. Movements are implemented, namely for the benefit of the company and / or to expand experience, insight, improve work productivity and the ability of company employees at PDAM Tirta Deli who retires and fill positions. By using the Oreste method in a decision support system that is able to process ordinal data or data in the form of ranks where a set of alternatives will be sorted according to criteria according to their level of importance. This employee mutation is carried out so that optimal company goals can be achieved to create employees who have high professionalism, so that they have the ability to adapt and anticipate flexible to all kinds of forms and nature of changes that are or will occur.